Development of an aggressive Miller Cycle engine with extended Late-Intake-Valve-Closing and a two-stage turbocharger. (February 2019) - He, Yongsheng; Liu, Jim; Sun, David; Zhu, Bin
This paper describes the development of an aggressive Miller cycle gasoline engine with stoichiometric combustion, a high expansion ratio of 12.5:1, a 65 crank angle degrees (CAD) longer duration Late-Intake-Valve-Closing (LIVC) cam, and a two-stage turbocharger. The full-load performance and part-load fuel consumption of the baseline and Miller cycle engines were assessed through engine dynamometer testing. The aggressive Miller cycle engine achieved the maximum Brake Mean Effective Pressure (BMEP) of 22 bar at 1500 rpm, which was enabled by the 65 CAD longer duration LIVC cam to further reduce the effective compression for controlling knock and by the two-stage turbocharger to provide significantly higher boost for maintaining and increasing trapped mass. It was shown that the more aggressive Millerization was realized while maintaining the specific output and advantages of current downsized boosted engines, such as lower friction and lower pumping losses. The aggressive Miller cycle engine achieved above 6% brake-specific fuel consumption (BSFC) reduction over the baseline turbocharged spark-ignition engine on average. The 65 CAD longer duration LIVC cam provided the benefit of pumping loss reduction with delayed intake valve closing and the benefit of hot residual dilution with relatively advanced intake cam phasing simultaneously, which provided the significant fuel economy improvement at non-knocking light-load conditions. Even without the latest technology enhancements and friction reduction methods on its base engine hardware, the aggressive Miller cycle engine achieved a very broad BSFC island of 230 g/kWh or lower, with the lowest BSFC of 223 g/kWh at 2000 rpm and 10 bar BMEP.